Diffused Scanning, Blind Stick & Rehabilitation - Tariq, Salma (International Journal of Endorsing Health Science Research, 2017)
Objective: Pakistan is a developing country and strive to provide cost effective solutions for rehabilitation and aid of visionless individuals with innovative technologies. The purpose of this study is to design and study the blind stick prototype implanted with modern technology. Method: Its significant characteristics is embedded photo-electric sensor that uses diffuse-reflective scanning to sense hindrance and feedback it to the high quality buzzer which can be heard easily furthermore it operates by only rechargeable 9V battery. This will enable the blind individuals to sense and detect the obstacle from 5mm to 127 mm distance with simplicity. Result: This prototype was used by a blind person in hall with obstacles. Results were tremendous and promising as the blind individual crossed the hall without tripping even a single time. Conclusion: It is portable, light weight, user friendly and extremely cost effective that is 4.77$ (500 Pakistan Rupees) only. It can be used not only in Pakistan but in other least developed countries as well. Blind as well as partially blind person can use it for walking in designated place independently.